Group photograph of Team Phoenix with recognition certificate - Eisele, John, photographer (Colorado State University. Libraries, 2016)
Team Phoenix.
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards